IPAC. Vlaams Aidscoördinaat. Jaarverslag... - Interprovinciaal Aidscoördinaat (IPAC) (Antwerpen : IPAC, 1988)
Fonds Suzan Daniel (FSD)
Periodiciteit: jaarlijks
Redactie: Nationalestraat 155, 2000 Antwerpen
Nederlands
Periodiek